Clinical features of Guillain–Barré syndrome with anti‐neurofascin 155 antibody. (4th August 2022) - Zhao, Ning; Chang, Sheng‐Hui; Zhang, Qiu‐Xia; Zhang, Lin‐Jie; Jiang, Shu‐Min; Zhai, Hui; Yang, Li
Abstract : Objective: Anti‐neurofascin 155 (NF155) antibody has been discovered in chronic demyelinating conditions. However, the positive rate and clinical description were insufficient in acute demyelinating conditions, such as Guillain–Barré syndrome (GBS). This study aimed to explore the positive rate of anti‐NF155 antibody in GBS patients and determine whether there were unique clinical characteristics in these patients. Materials & Methods: Serum anti‐NF155 antibody was detected from 94 GBS patients and 50 sex‐ and age‐matched healthy controls using cell‐based assay and tissue‐based assay with immunostaining of mouse teased sciatic nerve fibers. Clinical characteristics, laboratory data, and electrophysiology examinations were retrospectively collected. Results: Seven of 94 (7.45%) GBS patients were positive for anti‐NF155 antibody, and the main IgG subclass was IgG1. Compared with anti‐NF155 antibody‐negative GBS patients, anti‐NF155 antibody‐positive GBS patients had a higher GBS disability score at nadirs ( p = .010), higher modified Erasmus GBS outcome score ( p = .022), higher rate of abnormal compound motor action potential (CMAP) amplitude ( p = .002), higher frequency of prolonged F‐wave latency ( p < .001), lower frequency of abnormal sensory conduction velocity ( p < .001) and sensory nerve action potential amplitude ( p < .001), more axonal type ( p = .040), and poorer therapeutic effect ( p = .017). Conclusions: Anti‐NF155 antibody exists in a small portion of GBS patients. Anti‐NF155 antibody‐positive GBS patients possibly have a more severe clinical course, less sensory nerves involved, higher proportion of axonal type, poorer therapeutic effect, and worse prognosis, but the pathogenicity of the anti‐NF155 antibody in GBS needs further study.